Effects of Increasing Soybean Meal in Diets Based on Corn and Dried Distillers Grains with Solubles on Growth Performance and Carcass Characteristics of Late Finishing Pigs - Julia P. Holen; Robert D. Goodband; Mike D. Tokach; Jason C. Woodworth; Joel M DeRouchey (Kansas Agricultural Experiment Station Research Reports, 2021)
A total of 1,827 pigs (L337 × 1050, PIC; initially 215.8 ± 2.5 lb) were used to evaluate the effects of increasing soybean meal (SBM) in corn-DDGS-based diets on growth performance of late finishing pigs. Pens were blocked by BW and randomly assigned to 1 of 5 dietary treatments with 14 replications per treatment. Experimental diets were corn-based with 25% DDGS. Soybean meal levels increased from 0 to 16% in 4% increments replacing added feed grade AA. Pens of pigs were weighed to evaluate ADG, ADFI, and F/G. Data were analyzed with the GLIMMIX procedure of SAS and pen was considered as the experimental unit. The statistical model considered fixed effects of dietary treatment, linear and quadratic contrasts, and random effects of group and block. Overall, final BW of pigs marginally increased (quadratic;P<0.10) as SBM increased, with the greatest improvement observed when diets contained 8% SBM. However, there were no differences among treatments in overall ADG, ADFI, or F/G. Furthermore, there was no influence of increasing SBM on carcass characteristics. These results suggest that increasing SBM concentrations in diets that contain 25% DDGS did not influence growth performance of late finishing pigs.
Keywords: amino acids; crude protein; dried distillers grains with solubles; finishing pigs; soybean meal